Analysis of the Quality and Quantity of Ngade Lake as a Source of Clean Water in Ternate City - Nani Nagu; Badrun Ahmad; Sary Shandy (Indonesian Journal of Chemistry and Environment, 2023)
The Ngade Lake is one of the lakes on the island of Ternate. People use the lake as a tourist destination and fishing activity. This affects the lagoon's water quality, so measuring the water pollution parameters is necessary. This is because the lake can be used as a source of clean water. After all, the city of Ternate is currently experiencing limited water resources. The research was conducted to determine the availability of Ngade Lake as a source of clean water in terms of quality and quantity. The research method used in this study is experimental descriptive by conducting experiments and tests on the quality of Ngade Lake water and determining the amount of lake water through calculation from the measurement data. The water quality tests are carried out directly in Ngade Lake and the Laboratory physically and chemically. Physically includes taste, odor, temperatures, and temperatures. Chemical tests are conducted through COD, DO, pH, TDS, Density (CaCO3), metals (copper, iron, manganese), and other minerals. The results show that the quality testing of lake water meets the quality standards according to Permenkes No. 32 of the Year 2017, where the water in the middle of the lake has better water quality than the water on the lake's edge. The amount of water in Ngade Lake is measured at 3.394.744.000 litres. PDAM currently uses a pump with a discharge of 5 litres/second while the discharges of the water that is the reserve of water resources for Ngade Lake of 45 litres/second, so the water of the Lake of Ngade deserves to be used as a clean water source in terms of quality and quantity.   Keywords: Quantity, Quality, Water, Lake, Analysis